2021
DOI: 10.3390/ijms22179300
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Regulates Adipocyte Phenotype at Early Stages of Differentiation

Abstract: Obesity is a condition characterized by uncontrolled expansion of adipose tissue mass resulting in pathological weight gain. Histone deacetylases (HDACs) have emerged as crucial players in epigenetic regulation of adipocyte metabolism. Previously, we demonstrated that selective inhibition of class I HDACs improves white adipocyte functionality and promotes the browning phenotype of murine mesenchymal stem cells (MSCs) C3H/10T1/2 differentiated to adipocytes. These effects were also observed in db/db and diet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Adipogenesis is the process by which undifferentiated precursor cells differentiate into adipocytes. HDACs and HATs are components in epigenetic regulation; however, there are few reports of HDACs or HAT gene expression in adipocyte differentiation [39]. RT-qPCR assays revealed that HDAC1 and 3 were dynamically downregulated in response to TSA or VPA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis is the process by which undifferentiated precursor cells differentiate into adipocytes. HDACs and HATs are components in epigenetic regulation; however, there are few reports of HDACs or HAT gene expression in adipocyte differentiation [39]. RT-qPCR assays revealed that HDAC1 and 3 were dynamically downregulated in response to TSA or VPA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC3 knockdown could not only regulate adipocyte pro-inflammatory profile, but also promote the expression of transcriptional regulators related to adipogenesis, including Cebpb, Cebpa, Srebf1c, and PPARγ. 193 There is low HDAC6 expression in adipose tissues of humans with obesity and animal models of obesity. HDAC6 could regulate lipid storage by acetylating cell death-inducing DFFA-like effector C (CIDEC), a lipid droplet-binding protein.…”
Section: The Role Of Histone Acetylation In Metabolic Diseasementioning
confidence: 99%
“…Each group harbors specific functions, i.e. HDACs class I play a role in adipocyte differentiation as well as in establishing the metabolic characteristics of these cells [39,40].…”
Section: Environmental Pollution and Its Impact On Epigeneticsmentioning
confidence: 99%